Illocutionary Speech Acts of Assertive, Directive, Expressive, Commissive, and Declarative in the Tweets of Jibran Kholil Jibran Account - Husein, Syarif; Kholisin, Kholisin; Gintsburg, Sarali (Institut Agama Islam Negeri Curup, 2023)
This study aimed to describe the form of assertive, directive, expressive, commissive, and declarative illocutionary speech acts analysed based on the data collected. The method used was descriptive qualitative research. The data used were Arabic tweets contained in the twitter account @gbranit Ø¬Ø¨Ø±Ø§Ù† Ø®Ù„ÙŠÙ„ Ø¬Ø¨Ù€Ø±Ø§Ù† which totalled 30 tweets.Â Data collection used listening, note-taking, and documentation. The listening and note-taking techniques were carried out by collecting twitter tweets and selecting them for analysis. The analysis technique used Miles and Hubermanâ€™s interactive model comprising data collection, data reduction, data exposition, and conclusion drawing. This study revealed 30 data classified into 5 forms of illocutionary speech acts, namely 3 assertive speech acts, 6 directive speech acts, 13 expressive speech acts, 5 commissive speech acts, and 3 declarative speech acts. From all types of illocutionary speech acts, expressive speech acts were mostly used by speakers.